Verification That Mouse Chromosome 14 Is Responsible for Susceptibility to Streptozotocin in NSY Mice - Naru Babaya; Hironori Ueda; Shinsuke Noso; Yoshihisa Hiromine; Michiko Itoi-Babaya; Misato Kobayashi; Tomomi Fujisawa; Hiroshi Ikegami (International Journal of Endocrinology)
Introduction. Streptozotocin- (STZ-) induced diabetes is under polygenic control, and the genetic loci for STZ susceptibility are mapped to chromosome (Chr) 11 in Nagoya-Shibata-Yasuda (NSY) mice. In addition to Chr11, other genes on different chromosomes may contribute to STZ susceptibility in NSY mice. The aim of this study was to determine whether NSY-Chr14 contributes to STZ susceptibility and contains the STZ-susceptible region. Materials and Methods. A consomic C3H-14NSY strain (R0: homozygous for NSY-derived whole Chr14 on the control C3H background), two congenic strains (R1: the region retained proximal and middle segments of NSY-Chr14 and R2: the region retained a proximal segment of NSY-Chr14), and parental NSY and C3H mice were intraperitoneally injected with a single injection of STZ at a dose of 175 mg/kg body weight at 12 weeks of age. Blood glucose levels and body weights were measured at days 0, 1, 2, 4, 5, 7, 8, and 14 after STZ injection. At day 14 after STZ injection, pancreata were dissected and fixed. Results. After STZ injection, blood glucose levels were significantly higher in R0 mice than in C3H mice. However, blood glucose levels in R0 mice were not as severely affected as those in NSY mice. In R1 and R2 mice, blood glucose levels were similar to those in C3H mice and were significantly lower than those in R0 mice. Body weights were decreased in NSY and R0 mice; however, this change was not observed in R1, R2, and C3H mice. Although islet tissues in all strains exhibited degeneration and cellular infiltration, histological changes in NSY and R0 mice were more severe than those in R1, R2, and C3H mice. Conclusions. These data demonstrated that NSY-Chr14 was a STZ-susceptible chromosome and that STZ susceptibility was mapped to the distal segment of NSY-Chr14.